Sources of phosphorus for wintering beef heifer calves on dry bluestem pasture - Richardson, D.; Baker, F.H.; Menzies, C.S.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Forty head of choice-quality Hereford heifer calves were divided into four lots of 10 animals each on the basis of weight and type. Each animal was branded with an individual number and lot number. All animals grazed together on dry bluestem grass and were divided each day to receive their respective supplemental feed. Prairie hay was fed when snow covered the grass. The prairie hay averaged 1.67 pounds per head daily for the entire time of the experiment. Water and salt were available at all times.
Keywords: Beef; Phosphorus; Gain; Dry bluestem pasture